Writing and presenting research - Thody, Angela (London ; Thousand Oaks, Calif. : Sage Publications, 2006)
"This book presents a wide-ranging, introductory guide to the choices to be made in deciding how to communicate research findings in documents and presentations"--P. xv.
Conventions or alternatives? -- Principles for selecting appropriate writing and presentation styles -- Adapting to audience: adjusting for their aims -- Adapting to audience: adjusting for your purposes -- Arts and craft of writing -- Primary data -- Literature and methodology -- Quantified data -- Qualitative data -- Narrative data -- Beginnings and ends -- Citations: bibliographies, referencing, quotations, notes -- Becoming a presenter -- Getting into print -- Standing on the shoulders of giants: without violating their copyright -- Epilogue -- Appendix: research method for this book -- Bibliography.
Includes bibliographical references (p. 241-251) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Proposal writing in research; Report writing; Wetenschapsbeoefening; Schrijven; Wetenschappelijke publicaties; Uitgeven; Electronic books